New directions in Latin American Structuralism: a three-gap model of sustainable development - Gabriel Porcile; José Eduardo Alatorre; Martín Cherkasky; Camila Gramkow; Jo\~ao Romero (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2023)
Sustainable development implies reducing the gap in GDP per capita between center and periphery, increasing equality and protecting the environment. In this paper, we present a simple model within the Structuralist tradition that combines these three dimensions of sustainable development. We define three rates of growth: the minimum required to reduce inequality and eradicate poverty (yS); the maximum compatible with external equilibrium (yT); and the maximum compatible with a global carbon budget (yL). Estimations of these rates of growth for Latin America suggest that yS>yT>yL. We argue that a combination of industrial and technological policies, along with a major effort at income redistribution, is necessary for having yS=yT=yL, which defines a sustainable development path.
Keywords: F63; O14; O44; 330; sustainable development; Latin American Structuralism; growth and distribution